Kebijakan Pemindahan Ibu Kota Nusantara (IKN) Perspektif Pembangunan Berkelanjutan Berwawasan Lingkungan - Najwa Tasya (Savana, 2024)
This study aims to determine the problems arising from the development of the Indonesian Capital City and its development process from the perspective of environmentally sustainable development. The development and relocation of the Indonesian Capital City have raised pros and cons from various parties. This research method uses a normative legal approach. The results of the study are that the Policy for the Development of the Indonesian Capital City in East Kalimantan Province is considered to bring economic benefits, as well as provide potential for equitable development for areas outside Java, but also raises polemics related to environmental issues. Therefore, environmentally conscious development is needed, namely development that is oriented towards the management of natural resources while making efforts to protect them. Suboptimal development causes the creation of a less conducive environment, and can also result in an environment that is less supportive, hindering development in a particular region or area. The conclusion is that development policies must pay attention to environmental aspects so that the existence of the Indonesian Capital City will benefit the community and not become a burden on the environment.